THER-10. IMPACT OF BRAF MUTATIONAL STATUS ON THE EFFICACY OF IMMUNOTHERAPY FOR MELANOMA BRAIN METASTASES. (12th August 2019) - Lauko, Adam; Sagar, Soumya; Barnett, Addison; Wei, Wei; Chao, Samuel; Stevens, Glen; Peereboom, David; Yu, Jennifer; Murphy, Erin; Angelov, Lilyana; Mohammadi, Alireza; Suh, John; et al.
Abstract: BACKGROUND: BRAF mutations occur in 50% of melanoma patients. Targeted agents – BRAF and MEK inhibitors and immunotherapy improve survival of melanoma patients with BRAF mutations. These agents have intracranial efficacy as shown in clinical trials. However, the efficacy of immunotherapies (immune checkpoint blockade) in melanoma brain metastases and the correlation with BRAF status is not as well characterized. METHODS: We reviewed 351 patients with melanoma brain metastases treated at our tertiary care center between 2000 and 2018, 75 of which received immunotherapy with known BRAF mutational status. Two-year, 5-year, and median overall survival (OS) was calculated from the start of immunotherapy to compare the efficacy of immunotherapy in BRAF mutant and BRAF wild type patients using the log-rank test. RESULTS: At the time of diagnosis of brain metastasis, the median age was 61 (23–87) years, median KPS was 80 (50–100), number of intracranial lesions was 2 (1–15), and 79% had extra-cranial metastases. Sixty-three patients were treated with stereotactic radiosurgery (SRS), 27 underwent whole brain radiation (WBRT) and 21 underwent surgery. When treated with immunotherapy, BRAF mutant and BRAF wild type median survival was 15.7 months (95% CI=9.4 – 42.4) and 6.9 (95% CI=4.1– 26.7) months (p-value=0.205), respectively. Two-year BRAF mutant and BRAF wild type survival was 35% (95% CI=21 – 58) and 28% (95% CI=16 – 51), and 5-year survival was 22% (95% CI=10 – 46) and 23% (95% CI=11 – 47), respectively. CONCLUSIONS: Twenty percent of patients with BRAF mutant and BRAF wild-type patients treated with immunotherapy derive a long-term benefit from immunotherapy and multimodality treatment and are alive 5 years from diagnosis of brain metastases. This was rarely seen in the pre-immunotherapy era in melanoma brain metastases. There was no difference in outcome based on the BRAF mutational status with use of immunotherapy in melanoma brain metastases.